Manufacturing Growth and Agglomeration Effects - Fafchamps, Marcel (L'Actualité économique, 2018)
This paper investigates the effect of location-specific competition and diversity on manufacturing growth. Using detailed manufacturing data from Morocco, we find strong and robust evidence of agglomeration effects: competition is good for growth but diversity is not. However, in our study country these effects do not appear to be channelled through productivity or wages. First, agglomeration variables have opposite effects on growth and on individual firm productivity. Second, controlling for productivity directly does not reduce the significance or magnitude of agglomeration variables. In the study country, agglomeration variables measure something that is relevant for manufacturing growth, but it is not productivity. We also find that a rise in average productivity raises subsequent employment and investment, but has no effect on firm entry and exit.